Osthole ameliorates cognitive impairments via augmenting neuronal population in APP / PS1 transgenic mice. (March 2021) - Xiao, Honghe; Wang, Yuying; Wu, Yutong; Li, Hongyan; Liang, Xicai; Lin, Yin; Kong, Liang; Ni, Yingnan; Deng, Yan; Li, Yan; Li, Wanyi; Yang, Jingxian
Graphical abstract: Osthole ameliorates cognitive impairments via augmenting neuronal population in APP / PS1 transgenic mice Highlights: Osthole improved the environment of brain to protect neurons from death. Osthole promoted the proliferation of neural stem cells (NSCs) in the brain of APP/PS1 mouse. Osthole augmented the amount of mature neurons in the brain of APP/PS1 mouse. Abstract: Alzheimer's disease (AD) is a neurodegenerative disorder with notable factors of dysfunction in multiple neurological changes, encompassing neuronal loss in the frontal cortex and hippocampal regions. Dysfunction of proliferation and self-renewal of neural stem cells (NSCs) was observed in AD patients and animals. Thereby, mobilizing endogenous neurogenesis by pharmacological agents would provide a promising route for neurodegeneration. Osthole (Ost), a natural coumarin derivative, has been reported to exert extensive neuroprotective effects in AD. However, whether ost can facilitate endogenous neurogenesis against AD in vivo is still unknown. In this study, by using Morris water maze (MWM) test, hematoxylin-eosin (HE) staining, Nissl staining, immunofluorescence analysis and western blot, we demonstrated that oral administration of ost could improve the learning and memory function, inhibit neuronal apoptosis, elevate the expression of glial cell line derived neurotrophic factor (GDNF), synaptophysin (SYP) and postsynaptic density protein 95 (PSD95). Moreover, ost could remarkably enhance proliferation of NSCs and increase the amount of mature neurons in APP/PS1 transgenic mice. Together, our findings demonstrated that ost possessed the ability of promoting endogenous neurogenesis and ost could be served as a plausible agent to reverse or slow down the progress of AD.